Metals Are Integral to Life as We Know It - Rossetto, Daniele; Mansy, Sheref S. (Frontiers in Cell and Developmental Biology, 2022)
Investigations of biology and the origins of life regularly focus on the components of the central dogma and thus the elements that compose nucleic acids and peptides. Less attention is given to the inorganic components of a biological cell, which are required for biological polymers to function. The Earth was and continues to be rich in metals, and so investigations of the emergence and evolution of life must account for the role that metal ions play. Evolution is shaped by what is present, and not all elements of the periodic table are equally accessible. The presence of metals, the solubility of their ions, and their intrinsic reactivity all impacted the composition of the cells that emerged. Geological and bioinformatic analyses clearly show that the suite of accessible metal ions changed over the history of the Earth; however, such analyses tend to be interpreted in comparison to average oceanic conditions, which do not represent well the many niche environments present on the Earth. While there is still debate concerning the sequence of events that led to extant biology, what is clear is that life as we know it requires metals, and that past and current metal-dependent events remain, at least partially, imprinted in the chemistry of the cell.